(untitled) (Journal of Pharma Insights and Research, 2025)
UV spectrophotometric methods serve as essential analytical tools in pharmaceutical analysis for determination of risperidone, an atypical antipsychotic medication. Various stability-indicating UV spectrophotometric methods have emerged over the past decade, offering distinct advantages in terms of simplicity, cost-effectiveness, and reliability. The analytical wavelength for risperidone determination typically ranges between 275-280 nm, with methanol and 0.1N HCl being the commonly employed solvents. Most validated methods demonstrate linearity in the concentration range of 0.1-10 µg/mL, with correlation coefficients exceeding 0.999. Stability studies conducted under varied stress conditions including acid hydrolysis, alkaline hydrolysis, oxidative degradation, photolytic degradation, and thermal stress have revealed significant insights into the degradation behavior of risperidone. The primary degradation pathway involves cleavage of the benzisoxazole moiety, leading to the formation of 2-hydroxybenzoyl derivatives. Contemporary analytical methods achieve accuracy within 98-102% and precision with relative standard deviation below 2%. Recent developments have focused on improving method sensitivity, specificity, and applicability across different pharmaceutical formulations. The evolution of these analytical techniques has significantly contributed to quality control processes in pharmaceutical manufacturing and research applications. Combination of various analytical parameters and validation criteria paved pathway for robust methods suitable for routine analysis of risperidone in pharmaceutical dosage forms.